State of the Art in Nano-bioimaging (IntechOpen, 2023)
Nano-bioimaging is a real-time observation method for the study of biological processes in subcellular structures and entire cells. This technique aims to interfere as little as possible with life processes using nanoscale materials and probes. In this method, nanoscale photon source is often used for imaging, and 3D structure of the observed specimen is studied in detail without physical interference. Over the last decade, further boost in bioimaging has led to increase the nano-bioimaging impact that includes many improvements in the data analysis method, image processing, and molecular imaging technology. However, to increase the usage of nano-bioimaging, several developments in the field of diagnosis accuracy, photobleaching prevention, and controlling of the fluorescence resonance energy transfer (FRET) must be achieved. The purpose of this book is to provide a perspective on the current status of nano-bioimaging technologies.